2009
DOI: 10.1200/jco.2009.27.15_suppl.5500
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of the oral PARP inhibitor olaparib (AZD2281) in BRCA-deficient advanced ovarian cancer

Abstract: 5500 Background: Olaparib (AZD2281; KU-0059436) is a novel, orally active PARP inhibitor that induces synthetic lethality in homozygous BRCA-deficient cells. A phase I trial identified 400 mg bd as the maximum tolerated dose (MTD) with an initial signal of efficacy in BRCA-deficient cancers (ASCO 2008; abst 5510). The primary aim of this study was to test the efficacy of olaparib in confirmed BRCA1/BRCA2 carriers with advanced chemotherapy-refractory ovarian cancer. The secondary aim was to assess the safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Recently reported were the results of a phase II trial of the oral PARP inhibitor Olaparib (AZD 2281) in BRCA-deficient advanced ovarian cancer [ 86 ]. An international, phase II study examined two cohorts of patients that received oral olaparib in 28-day cycles, initially at the MTD, 400 mg bid (33 pts), and subsequently at 100 mg bid (24 pts).…”
Section: Poly-adp-ribose Polymerase (Parp) Inhibitorsmentioning
confidence: 99%
“…Recently reported were the results of a phase II trial of the oral PARP inhibitor Olaparib (AZD 2281) in BRCA-deficient advanced ovarian cancer [ 86 ]. An international, phase II study examined two cohorts of patients that received oral olaparib in 28-day cycles, initially at the MTD, 400 mg bid (33 pts), and subsequently at 100 mg bid (24 pts).…”
Section: Poly-adp-ribose Polymerase (Parp) Inhibitorsmentioning
confidence: 99%
“…The therapy was well tolerated, and investigators reported a 41% overall response rate in the patients of the first cohort, with a median progression-free survival of 5.7 months. The second clinical trial tested the same two sequential dose cohorts in women with BRCA-deficient advanced ovarian cancer [ 10 ]. At the time of the preliminary report, 33 patients were treated at the 400 mg dose, with response in 57.6% of patients and a median progression-free survival of 5.8 months.…”
Section: Major Recent Advancesmentioning
confidence: 99%
“…Multiple PARP inhibitors are currently being examined in phase II trials. Of interest, Audeh et al lately reported the interim analysis of a phase II study employing Olaparib in BRCA-deficient advanced ovarian cancer [ 57 ]. Overall 57% of patients demonstrated response to PARP inhibition, using either RECIST or CA-125 criteria.…”
Section: Parp Inhibitorsmentioning
confidence: 99%